Multi-objective optimal allocation of sediment resources under multiple uncertainties. (15th March 2021) - Li, Linqi; Zhang, Hongwu
Abstract: A model suitable for optimal allocation of sediment resources is utilized to cope with multiple uncertainties in the system and contradictions between allocation units. This approach incorporates inexact two-stage stochastic programming, probabilistic-possibilistic programming and fuzzy random intervals (ITPP-FRI) in an integrated framework. The multiple uncertainties of various parameters in this study are represented by the interval numbers with fuzziness and randomness. The model introduced the concept of possibility and necessity measures to address multiple uncertainties in the system, which are suitable for optimistic and pessimistic decision-makers, respectively. The model makes a tradeoff between multiple objectives including sediment siltation of each allocation unit, and economic benefits of the system. As demonstrated in the Weishan irrigation area, a number of alternative cases can be achieved at different probability levels and under varied sediment diversion scenarios. The result shows that the sediment allocation for the unit of desilting basins was significantly reduced by at least 4.3% compared with the current situation, and the units of transporting sediments to the fields and using them for producing building materials were increased by more than 15% and 5%, respectively. The sediment is allocated to the units in need and the channel siltation is reduced. According to the allocation results, a new pattern of regulating water delivery is put forward for irrigation area in this paper to meet the requirement of using limited water to transport sediment to each unit. Highlights: The ITPP-FRI model tradeoff the benefits of each sediment resources allocation unit. Reducing the impact of multiple uncertainties on the sediment resources allocation. Putting forward a new water delivery pattern based on the allocation results for the study area. Making sediment resourcization and slow down the canals siltation.